The Impacts of Cost Determinism in Architectural Foundation Design Education: An Analysis of Foundation Design Studio. (6th January 2016) - Lee, Seyeon; Tabb, Phillip; Rogers, Julia; Rybkowski, Zofia; Van Zandt, Shannon
Abstract: This research concerns teaching cost as an integral design determinant during architectural foundation design education. Design studio course description, syllabi, and studio projects of selected architectural foundation design programs were analysed and the U.S.-based architecture educators and design professionals were surveyed to investigate the degree to which their perspectives and methods of teaching cost conscious and economic design concepts in foundation design education. The result suggests that both academics and design professionals value in learning cost conscious and economic design concepts during foundation design education, however, overall systematic studio courses which teach cost as an integral design determinant were absent.